Carbonic anhydrases in normal gastrointestinal tract and gastrointestinal tumours - Kivelä, Antti J. (Baishideng Publishing Group Co., Limited, 2005)
Carbonic anhydrases (CAs) catalyse the hydration of CO(2) to bicarbonate at physiological pH. This chemical interconversion is crucial since HCO(3)(-) is the substrate for several biosynthetic reactions. This review is focused on the distribution and role of CA isoenzymes in both normal and pathological gastrointestinal (GI) tract tissues. It has been known for many years that CAs are widely present in the GI tract and play important roles in several physiological functions such as production of saliva, gastric acid, bile, and pancreatic juice as well as in absorption of salt and water in intestine. New information suggests that these enzymes participate in several processes that were not envisioned earlier. Especially, the recent reports on plasma membrane-bound isoenzymes IX and XII have raised considerable interest since they were reported to participate in cancer invasion and spread. They are induced by tumour hypoxia and may also play a role in von Hippel-Lindau (VHL)-mediated carcinogenesis.